Cold response and tolerance in cereal roots. (16th July 2021) - Zhou, Yaping; Sommer, Mauritz Leonard; Hochholdinger, Frank
Abstract : We summarize molecular and genetic mechanisms of cold acclimation and tolerance in cereal roots and highlight how phytohormones, microorganisms, and nutrients ameliorate cold stress. Abstract: Cold stress adversely affects plant growth and is a limiting factor in crop productivity. Temperature volatility as a consequence of climate change will increase the effects of cold stress on crop cultivation. Low temperatures frequently occur early after planting in temperate climates, and severely affect root development in cereals. In this review, we address the question of how cereal root systems respond to cold at different scales. First, we summarize the morphological, physiological, and cellular responses of cereal roots to cold stress and how these processes are regulated by phytohormones. Subsequently, we highlight current understanding of the genetic and molecular analyses of cold tolerance with emphasis on the role of cold-responsive genes in improving cold tolerance in cereal roots. Finally, we discuss the role of beneficial microorganisms and mineral nutrients in ameliorating the effects of cold stress in cereal roots. A comprehensive knowledge of the molecular mechanisms underlying cold tolerance will ensure yield stability by enabling the generation of cold-tolerant crop genotypes.